2015
DOI: 10.1007/s10340-015-0724-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of light attraction for the stored-product psocid, Liposcelis bostrychophila

Abstract: The psocid, Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelididae), is the most widespread psocid pest of stored products. Because L. bostrychophila has developed resistance to several chemical insecticides, it is important to investigate other integrated pest management (IPM) approaches, and a critical part of IPM programs is an effective monitoring program, Monitoring tools for psocids are limited, and few studies have been conducted on monitoring of psocids, with none on the attraction of lights fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A prior study by Diaz‐Montano et al . using the paired‐choice pitfall arena showed that L. bostrychophila adults were attracted by light, and, among the eight wavelengths tested, the 351 nm UV light wavelength was the only one that attracted more booklice than brewer's yeast 20 . Because brewer's yeast has been reported to be the best attractant for L. bostrychophila among more than 20 potential attractants tested previously, 19 it was concluded that 351 nm UV light is a strong attractant for them.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A prior study by Diaz‐Montano et al . using the paired‐choice pitfall arena showed that L. bostrychophila adults were attracted by light, and, among the eight wavelengths tested, the 351 nm UV light wavelength was the only one that attracted more booklice than brewer's yeast 20 . Because brewer's yeast has been reported to be the best attractant for L. bostrychophila among more than 20 potential attractants tested previously, 19 it was concluded that 351 nm UV light is a strong attractant for them.…”
Section: Discussionmentioning
confidence: 95%
“…19 Furthermore, Diaz-Montano et al studied the response of L. bostrychophila adults to specific light wavelengths and found that booklice responded strongly to wavelengths in the ultraviolet (UV) spectrum. 20 When light was compared with brewer's yeast, the only wavelength among eight tested that attracted more booklice than the yeast was 351 nm. The combination of light and brewer's yeast also showed certain synergistic attractive effects.…”
Section: Introductionmentioning
confidence: 99%
“…This represents the first time that such a short wavelength or any wavelength in the UV range has been tested with kissing bugs (the shortest wavelength tested in Pacheco-Tucuch et al [ 12 ] was 430 nm). In the psocid Liposcelis bostrychophila this wavelength (351 nm) elicited strong attractive responses [ 33 ]. Our results coincide with previous light sensitivity studies with the related species T. dimidiata that reported high attraction to blue (430 nm) with decreased attraction to increasing wavelengths [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methodology was adapted from Diaz-Montano et al [ 33 ] where it was used to test attraction of psocids to light. The arena was two petri dishes on top of each other to form a covered arena (14.5 cm diameter, 3 cm height) with two holes on either side (2 cm in diameter) leveled with the floor of the arena.…”
Section: Methodsmentioning
confidence: 99%
“…Attractants used for both monitoring traps and lure and kill can be chemical cues such as pheromones or kairomones or visual cues such as specific wavelengths of light [ 61 , 62 , 63 ]. Pheromones are often species and sex specific, which can be an advantage if targeting a specific pest, but pheromones are commercially available for only some of the common pest species, and not all species respond strongly.…”
Section: Application In Pest Managementmentioning
confidence: 99%